Approximated mathematical model of hydraulic drive of container upturning during loading of solid domestic wastes into a dustcart - Berezyuk, Oleg; Savulyak, Valeriy (Technical Sciences, 2017)
A simplified mathematical model of hydraulic drive of container upturning during loading of solid domestic wastes into a dustcart is proposed. Approximated analytical time dependencies of pressure in a delivery pipe of a hydrocylinder, angular velocity and the angle of container upturning are obtained. Approximated duration dependence of container upturning from main parameters of hydraulic drive is detected. Optimal values of main parameters of working organs, which ensure minimum time of container upturning during loading of solid domestic wastes into a dustcart are defined.